Formulação de produtos de higiene oral à base de biossurfactante e quitosana fúngica. - Farias, Juliana Martins de (2019)
The use of chemical surfactants in dental creams and mouthwashes, as well as fluoride and chlorhexidine, brings an alert due to the toxicity of these compounds. Chitosan, a potent antimicrobial agent, and biosurfactants, which have moist, foamy and antimicrobial properties, have been interested in the manufacture of products that meet the current market and are biocompatible. In the present study, three biosurfactants, two of them produced by the bacteria Pseudomonas aeruginosa UCP 0992 (BP) and Bacillus cereus UCP 1615 (BB) and one by the yeast Candida bombicola URM 3718 (BC), as well as the mucosal fungi chitosan were used in formulation of dental creams and mouthwashes instead of similar chemicals. For the formulations, the chitosan was characterized and the biosurfactants were produced and isolated. Mentha peperita essential oil (OEM) and commercial sodium fluoride were used as active ingredients. Minimum inhibitory concentration (MIC) was determined for the isolated test substances and for the formulation of mouthwashes and toothpastes, as well as MTT toxicity tests for L929 (mouse fibroblast) and RAW 264.7 (mouse macrophages) cell lines. The chitosan had a biomass yield of 60.6 mg/g, presenting characteristic bands to the polymer and degree of deacetylation of 80%. The biosurfactants BP, BB and BC reduced the water surface tension from 70 mN/m to 30, 29 and 26.5 mN/m, respectively. All the substances studied presented antimicrobial activity for the cariogenic microorganisms tested in the mouthwash formulations. The combinations between BC and BP with chitosan showed an additive effect for most of the microorganisms, being indifferent to E. coli and C. albicans. However, the association between BC and BB with the OEM had an additive effect only for E. coli and indifferent to the others. Toxicity was lower than commercial rinses. Toothpaste formulations containing biosurfactants, chitosan or sodium fluoride as active ingredients showed MIC for Streptococcus mutans. The combinations between BC and BP with chitosan showed an additive effect for S. mutans, being indifferent to BB with chitosan. All formulated toothpastes were non-toxic All formulations inhibited S. mutans cell viability in the formed biofilm, being similar to the commercial cream tested. The results validate that mouthwashes and dental creams with biosurfactants in association with chitosan are a safe, effective and natural alternative for the control of oral microorganisms in relation to commercial products available.